Perceptions of Malaria and Vaccines in Kenya - Ojakaa, David; Yamo, Emmanuel; Collymore, Yvette; Ba-Nguz, Antoinette; Bingham, Allison (Taylor & Francis)
Malaria is a leading cause of morbidity and mortality in Kenya. To confront malaria, the Government of Kenya has been implementing and coordinating three approaches - vector control by distributing insecticide-treated bed nets and indoor residual spraying, case management, and the management of malaria during pregnancy. Immunization is recognized as one of the most cost-effective public health interventions. Efforts are underway to develop a malaria vaccine. The most advanced (RTS,S), is currently going through phase 3 trials. Although recent studies show the overwhelming support in the community for the introduction of a malaria vaccine, two issues - culture and the delivery of child immunization services - need to be considered. Alongside the modern methods of malaria control described above, traditional methods coexist and act as barriers to attainment of universal immunization. The gender dimension of the immunization programme (where women are the main child caretakers) will also need to be addressed. There is an age dimension to child immunization programmes. Two age cohorts of parents, caregivers, or family members deserve particular attention. These are the youth who are about to initiate childbearing, and the elderly (particularly mother-in-laws who often play a role in child-rearing). Mothers who are less privileged and socially disadvantaged need particular attention when it comes to child immunization. Access to immunization services is often characterized in some Kenyan rural communities in terms of living near the main road, or in the remote inaccessible areas. Should a malaria vaccine become available in the future, a strategy to integrate it into the immunization programme in Kenya should take into account at least two issues. First, it must address the fact that alongside the formal approach in malaria control, there exist the informal traditional practices among communities. Secondly, it must address particular issues in the delivery of immunization services.
Full Terms & Conditions of access and use can be found at https://www.tandfonline.com/action/journalInformation?journalCode=khvi20
Keywords: Malaria; Vaccines; Community; Perceptions; Health education